The Educational Philosophy of the Pre-Service Elementary Teachers in the Teacher Professional Education Program - Natalia Destiana Putri; Ouda Teda Ena (Journal of Education Reseach and Evaluation, 2025)
High-quality teaching is a key factor in the success of a nation's education system. This study aims to identify the educational philosophies adopted by pre-service elementary school teachers and their implications for teaching approaches. This research employs a survey method involving 29 pre-service elementary school teachers enrolled in the Teacher Professional Education Program. Data were collected through an online questionnaire and analyzed using descriptive analysis with IBM SPSS software. The analysis results were interpreted based on mean scores to determine the respondents’ tendencies toward specific educational philosophies. The findings reveal that pre-service elementary school teachers exhibit the highest preference for progressivism (M = 4.31) and the lowest for essentialism (M = 3.29). Additionally, there is a stronger inclination toward modern educational philosophies rather than traditional ones. Teachers who lean toward progressivism prioritize student-centered learning, independent learning, collaboration, problem-solving, and reflective teaching practices. However, this study also indicates that pre-service teachers do not adhere to a single philosophy but rather demonstrate flexibility in their teaching approaches. These findings highlight the importance of understanding pre-service teachers’ educational philosophies for policymakers, educational institutions, and teacher educators in supporting the development of their teaching skills. The implications of this study emphasize the need for educational policies that promote flexibility in pedagogical approaches and curriculum reinforcement, equipping pre-service teachers with diverse educational philosophy perspectives to enhance teaching quality and the overall education system.